Mixed (carbonatic/siliciclastic) cycles in the Upper Member of the Mulichinco Formation (Cañadón Amarillo Field, central Neuquén Basin, Argentina): sequential implications and for reservoir characterisation (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The presence of carbonate strata within sili- ciclastic-dominated marine successions (i.e. mixed carbonate-siliciclastic successions) poses serious challenges for palaeoenvironmental reconstructions and reservoir characterization, and unambiguous interpretations can emerge only when the spatial vs. temporal relationship between carbonate production and siliciclastic input is well understood. This study integrates sedimentology and high-resolution sequence stratigraphy in order to better understand the temporal/spatial relationships and controls in the origin of a Lower Cretaceous, mixed carbonate- siliciclastic succession in the subsurface of the Neuquén Basin, west-central Argentina (Figs. 1, 2). This mixed succession, so-called Upper Member of the Mulichinco Formation, accumulated in a shallow, epeiric sea during third-order highstand conditions (Fig. 3), and is presently widely distributed in the central part of the basin, both in outcrops and subsurface (Schwarz et al., 2009; Schwarz et al., 2011). The study area, covering an area of about 80 km2, is located in the Cañadón Amarillo hydrocarbon field (Fig. 4), where this unit has been in production since the 1970’s. This study is based on a detailed description and interpretation of four cored wells (three of them covering the entire unit), complemented with calibrated well-log suites from additional 22 wells (Fig. 5).The Upper Member of the Mulichinco Formation (65-80 m thick) has a cyclic alternation of relatively thick (up to 16 m) siliciclastic packages and thinnercarbonate-dominated intervals (Fig. 6). Three facies associations were identified within the siliciclastic packages, and they are inferred to represent shoreface, offshore-transition, and offshore settings in an open marine system influenced by storm- and fair-weather waves. The lower-shorefacefacies association (Fig. 7) is composed of amalgamated, siliciclastic sandstone beds (with minor contribution of carbonate particles) mostly having hummocky cross-stratification, horizontal lamination or ripple cross-lamination. Bioturbation varies from low to high and the trace fossil suite (Arenicolites, Gyrochortes, Palaeophycus, Ophiomorpha, Skolithosy ?Macaronichnus) is interpreted to represent an Skolithosichnofacies (MacEachern et al., 2007). The offshore-transition facies association groups intensely bioturbated muddy sandstones and less bioturbated (i.e. better preserved) sandstone-rich heterolithics (Fig. 8), with occasional medium-bedded sandstone beds (< 15 cm thick) having HCS and rippled tops. Siliciclastics largely dominate within these sediments, but bioclasts (mostly from oysters) can be common locally. The assemblage of trace fossils (Planolites, Palaeophycus, Thalassinoides, Teichichnus, Phyco- siphon, Ophiomorpha, Schaubcylindrichnus y As- terosoma) is attributed to represent a Proximal Cruzianaichnofacies (MacEachern and Bann, 2008), and, together with the sediments, reflect a storm- dominated offshore-shoreface transition, between the storm and fair-weather wave bases (Reading& Collinson, 1996). In turn, the offshore facies association comprises mostly massive or laminated mudstones, as well as mudstone-dominated hetero- lithics. In the latter, very thin-bedded siltstone beds with wavy tops are abundant, likely reflecting the distal ends of storm-related flows.Carbonate-dominated intervals are composed of two facies associations that collectively are inferred to represent subenvironments within acarbonate ramp, namely shallow (inner) and middle sectors of it. The shallow-ramp facies association is characterized by cross-bedded ooid-skeletal grainstones/packstones, with subordinated skeletal rudstones and packstones (Fig. 10). Bioclasts derived mostly from mollusks and echinoids, whereas terrigenous material is less than 25%. These sediments deposited in open-marine high-energy settings, likely shoals and intershoals areas (Rankey y Reeder, 2011; Christ et al., 2012). In contrast, the middle-ramp facies association is composed of mud- dominated textures, mostly skeletal wackestones and floatstones (Fig. 11). They are massive, but argillaceous seams might create a nodular aspect. Bioclasts from epibenthic (oysters) and endobenthic bivalves, as well as from serpulids and echinoids are dominant, but glauconite and intraclasts are locally abundant. Compared to the previous association, these sediments were deposited in lower energy and deeper parts of the ramp.The nature of key stratigraphic surfaces, facies associations distribution and analysis of stacking patterns within this cyclic carbonate/siliciclastic succession suggest that the siliciclastic- and carbonate-dominated depositional systems were not coeval, but replaced over time. Correlation panels show that individual carbonate and siliciclastic hemicycles extend across the entire area and lateral transition between them were not recorded (Figs. 12, 13). Carbonate packages are invariably bounded by sharp, erosive surfaces (Fig. 14a,b), which are interpreted to represent transgressive ravinement surfaces (Swift, 1968; Nummedal and Swift, 1987). Facies associations in these hemicycles suggest a deepening-upward trend, whereas in the overlying siliciclastic packages the stratal patterns indicate normal (i.e. not forced) regressive conditions (Fig. 15). Therefore, the seven small-scale cycles (plus two incomplete cycles) recorded in the Upper Member of the Mulichinco Formation (3-18 m thick) are interpreted to represent high-frequency sequences (nomenclature following Zecchin and Catuneanu, 2013), comprising relatively thin, transgressive, carbonate-rich hemicycles and thicker, siliciclastic regressive hemicycles (Fig 16). The non-erosive boundary between both hemicycles (Fig. 14c) could correlate with the maximum flooding surface (Van Wagoner et al., 1990), or being slightly younger, as it reflects enough terrigenous supply to dilute carbonate productivity (Abbot, 1997). In this context, it isconsidered equivalent of a downlap surface (Fig 16). These high-frequency sequences were most likely controlled by short-term, low-amplitude, relative sea-level changes, and the thickness of transgressive hemicycles could have been influenced by carbonate productivity and/or rate of transgression.The results of this study provide with a more accurate reservoir characterization of this mixed (and complex) succession. Two reservoir-type facies associations were identified, namely the lower- shoreface and shallow-ramp facies associations. The understanding of key reservoir attributes, such as geometry, thickness, connectivity and internal heterogeneity were improved with this study. Additionally, the findings of this work provided with a high-resolution sequence-stratigraphic model that help predicting the occurrence of the reservoir- type facies within a high-frequency sequence. The integration of all these elements within a geological model could contribute to define for example the most efficient development strategy for the reservoir horizons (e.g. vertical versus horizontal wells) which would, eventually, impact in the recovery factor of the field.
Keywords: Carbonate/Siliciclastic Cycles, High- Resolution Sequence Stratigraphy, Reservoirs, Mulichinco Formation, Neuquén Basin.